ART IKARIA, Atheras Project, Ikaria, 2025 - Pericleous, Vicky (My University, 2025)
Ikaria 2025 - The Atheras Project: The ATHERAS PROJECT team is an artistic and intellectual movement that explores the limits of human intervention in the natural landscape. It approaches public space as a place of memory, experience, and collective identity in a dangerous transition. Following two successful events in Athens, Atheras Project Act One & Atheras Project Act Two – I n t e r v e n t i o | Space-Time-Memory , is organizing a group art exhibition in August 2025 in Ikaria: Art Ikaria – The Atheras Project Place and Memory are concepts that inspire artistic creation, enabling artists to express themselves through their work and allowing each of them to tell their own story. 50+ artists with a common theme, but with different approaches and means of expression, create a shared story. Their coexistence and interaction in this group exhibition create a visual dialogue, a conversation of multiple narratives, placing their works in the present with common concerns about the environment, the limits of human intervention in the natural landscape and the cultural heritage of each place, and looking forward to a creative dialogue that flows from the multidimensional dynamic relationships of individuals and groups with the place and its experiences. The works of more than 50 artists, using different media such as painting, photography, sculpture, engraving, installations, video art, ceramics, mosaics, etc., will be displayed in a large parallel exhibition combining indoor and outdoor spaces, as well as locations in the wider area of Ikaria in the form of an art trail – Ikaria Art Walk – forming the core of a cultural dissemination of ideas and art events. An interactive cultural dialogue between artists, island residents, and visitors to Ikaria. During the local exhibitions between August 11 and September 6, 2025, Art Ikaria 2025 will be enriched with a program of parallel events scattered throughout the island, hosting events, open studios for artists, live music, and more.
Keywords: Arts; Place & Memory; Site Specific Interventions; Installations/Screenings in Public Space